Inflation and fiscal deficits in sub-Saharan Africa - Bleaney, Michael; Francisco, Manuela (Oxford University Press, 2016)
Inflationary performance in sub-Saharan Africa since 1996 is examined. Median inflation has tended to be higher than in other regions of the developing world, such as MENA and Latin America. Inflation is highly persistent and is higher in countries that are less politically stable, in those without hard-peg exchange rate regimes, and in those with larger fiscal deficits. Inflation has declined over time, at least at the upper end of the distribution. There is no evidence that commitment devices such as inflation targeting have reduced inflation, but in SSA the sample is confined to two countries. Inflation typically spikes after a devaluation, and is sensitive to supply-side shocks. Movements in the real price of oil and rice (but not maize) have significantly affected the inflation rate. In countries that are poor in oil and minerals and therefore more reliant on agriculture, output growth is negatively correlated with inflation, presumably because, when the harvest is good and agricultural output is high, the extra supply reduces food prices. Fiscal balances also display considerable persistence and are more favourable in resource-rich and politically stable countries and in those with hard-peg exchange rate regimes, and have improved over time.